Wild Edible Fruits of Nepal - Gautam, Ratna Silwal; Shrestha, Sudha Joshi; Shrestha, Ila (International Journal of Applied Sciences and Biotechnology, 2020)
A review was done on the wild edible fruit plants of Nepal. Altogether 199 wild edible fruit plant species belonging to 139 genera representing 67 families documented from west Nepal to east Nepal. Study shows that people are using the wild edible fruits collected from forest resources as a part of their livelihood. People consume those wild fruits in different forms such as raw fruit, vegetables, pickles, spices and oil. Some species are taken in more than one form. Int. J. Appl. Sci. Biotechnol. Vol 8(3): 289-304